2012
DOI: 10.1002/aqc.2235
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mangrove areas for fisheries enhancement; population assessment in a patchy habitat

Abstract: 1. Small-scale fisheries are an important element of the ecosystem goods and services that mangrove habitats provide, especially to poorer coastal communities that rely most on natural resources, and have similar values to payments for ecosystem services (PES) under carbon-trading schemes.2. In advance of fishery-enhancement trials for the mud crab Scylla olivacea, a mark-recapture study was conducted to estimate population size and turnover in 50 ha of isolated mangrove on Panay Island, Philippines. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…Preliminary investigations demonstrate that restocking with juvenile mud crabs (Scylla olivacea and S. serrata) increases fishery productivity by 46%, from 48 ± 3 g per gear per day for wild crabs to 68 ± 3 g per gear per day for total wild and restocked crabs (Lebata et al 2009). Mean recapture rates range from 35-42%, highlighting the benefits of releasing juveniles for both long-term stock improvement (more than 50% of released crabs remain un-captured, although some likely suffer mortality) and seasonal improvement in fishery productivity (Lebata et al 2009;Lebata et al 2012).…”
Section: Replanted Mangrove System Misamis Occidental Philippinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary investigations demonstrate that restocking with juvenile mud crabs (Scylla olivacea and S. serrata) increases fishery productivity by 46%, from 48 ± 3 g per gear per day for wild crabs to 68 ± 3 g per gear per day for total wild and restocked crabs (Lebata et al 2009). Mean recapture rates range from 35-42%, highlighting the benefits of releasing juveniles for both long-term stock improvement (more than 50% of released crabs remain un-captured, although some likely suffer mortality) and seasonal improvement in fishery productivity (Lebata et al 2009;Lebata et al 2012).…”
Section: Replanted Mangrove System Misamis Occidental Philippinesmentioning
confidence: 99%
“…Site selection for stock enhancement programs is also critical for insuring the success of the program (Lorenzen 2008). Lebata et al (2012) demonstrated that the Ibajay mangrove system in the Philippines was suitable for mud crab release because food supply and dietary composition were sufficient, as indicated by high specific growth rates of released crabs. The system was also relatively closed, which excluded predatory sharks and macaques, and the initial wild crab density was low (12-33 per crabs ha) compared to similar systems, demonstrating that the system was likely to be below carrying capacity and that the opportunity for stock enhancement was significant (Lebata et al 2012).…”
Section: Replanted Mangrove System Misamis Occidental Philippinesmentioning
confidence: 99%
“…Ekosistem mangrove memiliki produktivitas tinggi yang memperkaya kawasan pesisir, sehingga berpengaruh terhadap peningkatan produksi perikanan tangkap dan perikanan budidaya tambak tradisional (Gevana et al, 2015). Potensi ekosistem yang besar tersebut telah mengalami laju eksploitasi yang signifikan dengan memanfaatkannya tanpa memperhatikan aspek keberlanjutan ekosistem (Lebata et al, 2012). Menurut Fitri & Anwar (2014) Indonesia mengalami degradasi ekosistem mangrove pada 2 sampai 3 dekade ini sekitar 50%, dari luas total 6,7 juta ha dan sekarang tinggal ± 3,2 juta ha atau 22,6% luas mangrove dunia (Giri et al, 2011).…”
Section: Pendahuluanunclassified
“…Ekosistem mangrove berperan besar dalam menjaga keberlanjutan dan keseimbangan ekosistem pantai dan pesisir (Marchand, 2017;Nguyen & Parnell, 2017). Mengingat besarnya manfaat ekosistem hutan mangrove, terkadang pemanfaatannya tidak memperhatikan daya dukung lingkungan (Lebata et al, 2012) bagi keberlanjutan sumberdaya, baik secara biologis, fisik, ekologis maupun secara ekonomis (Rakhfid & Rochmady, 2013;Rochmady, 2015b). Aktivitas pemanfaatan berlebihan dapat menimbulkan dampak merugikan bagi masyarakat (Zaitunah, 2002;Agusrinal et al, 2015).…”
Section: Akuatikisleunclassified